THEORETICAL FOUNDATIONS OF SUSTAINABLE DEVELOPMENT IN THE HEALTH SECTOR OF UKRAINE - Savchuk , L.M. (The actual problems of regional economy development, 2017)
This article aims at deepening the theoretical foundations of the development of the health sector in the conditions of realization of the strategy of sustainable development of the state. Summarizes the notional and terminological apparatus of the modern economic science of health. Clarified categories “human health”, “public health”, “health”, “healthcare”, “health”, “development”, “sustainable development”. Introduced the concept of “sustainable development of the health sector”. The article generalises theoretical approaches to understanding issues in health care.